An economic analysis of rapeseed-mustard in Ganganagar district of Rajasthan - Singh, Hemendra; Singh, N.K.; Bairwa, K.C. (Annals of Agricultural Research, 2016)
The present study was conducted to analyze the economics of rapeseed-mustard. The study area was selected on the basis of highest area and production under this crop. Rajasthan is one of the major rapeseed-mustard producing states of India. Rapeseed-mustard was selected on the basis of highest area among oilseed crops. The cost A1 was found to be increasing with the increase in farm size. The cost B1 is computed as the sum of cost A1 and the value of interest on fixed capital. The cost B2, comprises the rental value of owned land, the rent paid for leased in land and cost B1. In case of cost C1, imputed value of family labour and cost B1 included with this cost. The cost C2 indicate the contribution of family labour in the various operations performed on a cultivation of rapeseedmustard crop. The overall cost of production per quintal of rapeseed-mustard was computed to be Rs. 1502 on C3 basis. The cost of production on C3 per quintal on small, medium and large farms was Rs. 1675, Rs. 1497 and Rs. 1334, respectively. The average productivity of rapeseed-mustard was 18.4 quintals per hectare. On an average, the farm business income from rapeseed-mustard cultivation was Rs. 38526. On overall basis, family labour income was worked out to be Rs. 22,160 per hectare. The overall net income from rapeseed-mustard cultivation was Rs. 19178 per hectare. The return per rupee was Rs. 1.59. The net returns decreased with increase in size of holding mainly because of higher costs incurred on medium and large farms. The return per rupee increased with increase in size of holding